ORAL HEALTH EVALUATION OF ELDERLY PEOPLE AT THE BETTER AGE CONVENIENCE CENTER IN THE MUNICIPALITY OF ALTAMIRA-PA - Gonçalves Luis, Lorrany; Stephany Costa Falcão, Mahaya; Celerino dos Anjos Lima, Mírian; Celerino dos Anjos, Noemi; Henrique Leal Carneiro, Pedro; Haykel Claro dos Santos Silva, Danyela (Health and Society, 2023)
To describe the sociodemographic conditions, need for oral rehabilitation and access to dental services for elderly people enrolled in the Senior Living Center in the city of Altamira-Pa. A social action was carried out with 61 elderly people, 47 female and 14 male. As for the need for oral rehabilitation, the elderly of both genders used dental prosthesis total (72,1%) and partial (50,8%) were considered inappropriate 27,9%. Edentulism was evidenced as a public health problem for the elderly and that the elderly group, both male and female, do not have access to dental services.